Political Recruitment of the Prosperous Justice Party in Determining Legislative Candidates for the 2024 Election in Pontianak City - Andriani, Vini Olivia; Asmadi; Padilah, Ahirul Habib; Patriani, Ira; Nge, Herri Junius (Pencerah, 2025)
The Prosperous Justice Party (PKS) is one of the parties participating in the 2024 Legislative Election in Pontianak City. Political recruitment, particularly in the recruitment of legislative candidates, is crucial for the party's continued success in participating in the Legislative Election. In its recruitment process, the Articles of Association (AD-ART) serve as the primary foundation for the PKS Party in conducting its political recruitment. This study aims to determine the political recruitment process carried out by the PKS Party in determining its legislative candidates for the 2024 Legislative Election in Pontianak City, and whether it complies with the AD-ART. The research method used in this study is a qualitative descriptive research method. The results of this study indicate that the recruitment process uses an open and closed recruitment system. The open recruitment process carried out by the PKS Party is generally aimed at all Indonesian citizens who have the interest and potential to become legislative candidates without exception. Meanwhile, the closed recruitment process is specifically for cadres who have been fostered and the party structures who then nominate themselves for legislative candidates. In the process of determining its legislative candidates, the PKS Party considers the quality, capacity, potential, and track record of each candidate. Apart from that, in the legislative candidate recruitment process, there was 1 point that was not implemented in accordance with the PKS Party's Articles of Association/Bylaws in its recruitment process.